2014
DOI: 10.1136/bmjopen-2014-005245
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime alcohol use and overall and cause-specific mortality in the European Prospective Investigation into Cancer and nutrition (EPIC) study

Abstract: ObjectivesTo investigate the role of factors that modulate the association between alcohol and mortality, and to provide estimates of absolute risk of death.DesignThe European Prospective Investigation into Cancer and nutrition (EPIC).Setting23 centres in 10 countries.Participants380 395 men and women, free of cancer, diabetes, heart attack or stroke at enrolment, followed up for 12.6 years on average.Main outcome measures20 453 fatal events, of which 2053 alcohol-related cancers (ARC, including cancers of upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 30 publications
6
71
0
2
Order By: Relevance
“…For light-to-moderate alcohol consumption (up to 30 g/day), our results were similar to the EPIC study conducted by Ferrari et al ,3 which showed no association in any of the cause-specific mortalities studied (CVD, ARC, external causes of deaths) compared with 0.1–4.9 g/day of alcohol intake. In contrast with this EPIC study, we did not observe a statistically increased risk in any of the cause-specific mortalities studied among abstainers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For light-to-moderate alcohol consumption (up to 30 g/day), our results were similar to the EPIC study conducted by Ferrari et al ,3 which showed no association in any of the cause-specific mortalities studied (CVD, ARC, external causes of deaths) compared with 0.1–4.9 g/day of alcohol intake. In contrast with this EPIC study, we did not observe a statistically increased risk in any of the cause-specific mortalities studied among abstainers.…”
Section: Discussionsupporting
confidence: 91%
“…Alcohol-attributable deaths are highest in the European Region and particularly in high-income countries within Europe 2. In two recent studies, heavy alcohol consumption increased mortality from alcohol-related cancer (ARC), external causes and ‘other causes’ (external causes of deaths),3 4 while no association was observed for coronary heart disease (CHD) and other cardiovascular diseases (CVDs) 3. A J-shaped association between alcohol and all-cause mortality was been observed in two recent meta-analyses of prospective studies 5…”
Section: Introductionmentioning
confidence: 98%
“…The European Prospective Investigation on Cancer and nutrition (EPIC) study monitored 380,395 participants for 13 years (4,187 CVD deaths) (274). Female never-drinkers were at increased risk of CVD death (RR: 1.31; 95% CI: 1.13 to 1.53) compared with moderate drinkers (0.1 to 4.9 g/d); but the association was not significant for male never-drinkers (RR: 1.20; 95% CI: 0.89 to 1.62).…”
Section: Macronutrients Foods and Cvd Risk Factorsmentioning
confidence: 99%
“…Alcohol has been recognised as a major contributor to cancer mortality 5 42. The study of the links between PA and cancer is a recent field and current evidence shows that there is a robust decreased risk with increased PA for breast and colon cancers and perhaps several other cancer sites (eg, ovarian, lung and prostate cancers) 25 43 44.…”
Section: Discussionmentioning
confidence: 99%